PENGEMBANGAN METODE PENGAJARAN ENERGI TERBARUKAN DI SDN 201 SUKALUYU KOTA BANDUNG - Suryaman, Nia Nuraeni; Ash Siddiq, Raden Herdian Bayu; Ardiansyah, Neris Peri (Jurnal Abdi Insani, 2024)
This PKM activity focuses on the development and implementation of innovative teaching methods for renewable energy education at SDN 201 Sukaluyu, Bandung. Acknowledging the importance of early exposure to the concept of sustainability, this community service activity explores effective pedagogical approaches to engage elementary school students in understanding renewable energy sources, technology, and its significance for a sustainable future. This PKM activity investigates the impact of combining hands-on activities, project-based learning, and interactive learning experiences, which potentially includes the integration of renewable energy systems within the school environment. By analyzing student engagement, knowledge acquisition, and attitude changes towards renewable energy and sustainable practices, this PKM activity aims to contribute to the development of effective teaching strategies for integrating renewable energy education into the elementary school curriculum, foster environmental awareness, and promote a future generation equipped to tackle global energy challenges. The stages of the method carried out in this community service program are socialization, training, technology implementation, mentoring, evaluation, and program sustainability. The community service program (PKM) aimed at developing renewable energy teaching methods at SDN 201 Sukaluyu, Bandung City, successfully introduced the concept of renewable energy to fifth-grade students. Teaching aids and prototypes introduce students to hydroelectric power plants (HEPP), wind power plants (WPP), and solar power plants (SPP) through a series of socialization activities, training, and technology implementation. The evaluation results show that although 70% of students have heard about renewable energy, 60% of them still do not fully understand its benefits. The conclusion of this community service program indicates that this activity can enhance students' understanding of renewable energy.